Tribulus terrestris can suppress the adverse effect of toluene on bovine and equine ovarian granulosa cells. Issue 11 (13th July 2022) - Fabová, Zuzana; Tarko, Adam; Harrath, Abdel Halim; Alwasel, Saleh; Kotwica, Jan; Sirotkin, Alexander V.
Abstract: Influence of oil‐related product toluene and herbal remedy puncturevine Tribulus terrestris L. (TT) on female reproduction is known. Yet, mechanisms of their action on ovaries in different species and potential protective effect of TT against adverse toluene action remain to be established. We studied the effect of toluene, TT, and their combination on ovarian granulosa cells from two mammalian species (cows and horses). Viability, markers of proliferation (PCNA) and apoptosis (bax), steroid hormones, IGF‐I, oxytocin, and prostaglandin F (PGF) release were analyzed by trypan blue exclusion test, quantitative immunocytochemistry, and EIA/ELISA. Toluene suppressed all analyzed parameters. In both species, TT stimulated proliferation and reduced progesterone, oxytocin, and PGF. In horses, TT inhibited testosterone and IGF‐I. In both species, TT supported toluene effect on viability, steroids, IGF‐I, and PGF, and inverted its action on apoptosis. In cows, TT promoted toluene effect on proliferation. In horses, TT supported toluene effect on oxytocin but suppressed its influence on proliferation. In both species, toluene induced inhibitory action of TT on viability, steroids, IGF‐I, and PGF, and prevented its stimulatory action on proliferation. In cows, toluene supported inhibitory action of TT on oxytocin and prevented its stimulatory action on apoptosis. In horses, toluene induced stimulatory effect of TT on apoptosis. Our results indicate potential toxic toluene effect on farm animal ovaries, applicability of TT as a biostimulator of farm animal reproduction and as a protector against the adverse influence of toluene on female reproduction.